Prevalence and factors associated with nutritional deviations in women in the pre-pregnancy phase in two municipalities of the State of Rio de Janeiro, Brazil - Daniele Marano; Silvana Granado Nogueira da Gama; Rosa Maria Soares Madeira Domingues; Paulo Roberto Borges de Souza Junior (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
OBJECTIVE: To assess the prevalence and potential factors associated with pre-pregnancy nutritional status of women. METHODS: This is a cross-sectional study carried out between December 2007 and November 2008 with 1,535 women in the first trimester of pregnancy and randomly selected in health units of the Brazilian public health system (SUS) in the municipalities of Queimados and Petrópolis in the State of Rio de Janeiro. The diagnosis of nutritional deviations was based on the Body Mass Index, according to the classification of the Institute of Medicine, and the following categories were obtained: underweight, normal weight, overweight and obesity. In the statistical analysis, the multinomial logistic regression model was used and an odds ratio and confidence interval of 95% were estimated. RESULTS: The sample included women between 13 and 45 years. The prevalence of underweight, overweight and obesity were 10, 18 and 11%, respectively. Women living in Queimados, adolescents, women who did not live with a partner and smokers had a higher proportion of low pre-pregnancy weight. There was an association between hypertension, overweight and obesity. Adolescents presented lower chance to overweight and obesity. Living in Queimados reduced the odds of overweight. CONCLUSION: The proportion of pre-pregnancy nutritional deviations was high, and recognizing factors that lead to them is very important for an early identification of women at nutritional risk, with view to interventions to reduce the adverse effects of malnutrition on maternal and child health.